The Light Transmittance and Electrical Conductivity Properties of Gelam Wood Carbon Nanosheet and Its Derivatives - Nyimas Febrika Syabaniah; Nirwan Syarif; Dedi Rohendi; Mellysa Wandasari; Wara Dyahpita Rengga (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
The research on the preparation and characterization of transparent electrode carbon nanosheet based gelam woods bark doped with SnO2-SbO2. XRD analysis showed peaks at 2θ = 26.87°; 26.38° for carbon crystal and at 2θ = 28.59°; 34.35° for SnO; at 2θ = 51.99°; 62.20° for SbO2. SEM analysis show that the carbons have self-curling sheets that indicated defection in their surface. The carbons have self-curling sheets, which indicated that their surfaces have many defects. It assumed when exfoliation process is undergone, the layers was significantly decreased as sonication process and formed rCNSO. Diffractogram XRD of CNS, CNSO and rCNSO showed diffraction peak at 2θ= 24.3°. Oxygen functional group in CNSO might cause an increasing of interlayers distance between hexagonal networks of carbon layer. It also affect electrical resistant or the conductivity. FTIR spectrum indicate that CNSO has several  absorption peaks at for –OH stretch for free water and alcohol. At 2337 cm-1 was showed a carboxylic acid peaks and C=C stretch at 1627 cm-1. There is a skeletal vibration rCNSO structure occurred at each graphene layers. The ratio of the integrated intensities (IG/ID = 0.89 for CNS, 0.85 for CNS-O, and 0.93 for rCNSO of Raman spectroscopy is significantly high. Electrical conductivity of transparent electrode ranges from 1.26 x 10-7 Scm-1 – 5.03 x 10-7Scm -1. The highest conductivity value on transparent electrode contained rCNSO.This result inferred that the usage of rCNSO can increase electrical conductivity. Therefore, the higher value of electrical conductivity can be related to the value of La. The average maximum absorption wavelength is observed at 350-530 nm which means that the transition of the electronic transition π→π* occurs in the conjugated carbons system. Electrical conductivity of transparent electrode ranges from 1.26 x 10-7 Scm-1 – 5.03 x 10-7 Scm -1. The highest conductivity value on transparent electrode contained rCNSO. The band gap values in the transparent electrode range from 2 eV - 3 eV which means they have conductor – semiconductor characters.Keywords: Nanosheet, Carbon, Electrical, Conductivity, Derivate.